News agencies : Anachronism or lifeblood of the media system? - Jukes, Stephen (Abingdon, Oxon; New York, NY : Routledge, 2022)
"This book explores the role of international news agencies and investigates whether they have been able to adapt to the contemporary media landscape following the disruption wrought by fake news, social media and an increasingly polarised public discourse. News Agencies addresses the key players in the industry, beginning with the 'big three' (Reuters, The Associated Press and Agence France-Presse) and then moving on to the newest global player, Bloomberg. It also explores the role of alternative providers of international news which are seeking to challenge the Western-centric perspective of the agencies. Drawing on interviews with senior editors, Jukes investigates the challenges agencies face in terms of their editorial strategy and business models in today's social media context. At a time when there is widespread distrust in the media and agencies are relying increasingly on user-generated content as a source for news, Jukes critically explores the role of the agencies in the debate over fake news and policies on objectivity, impartiality and verification. Shedding light on a sector of the news industry that has steadfastly remained out of the public spotlight, this book will be of interest to students and academics in the fields of journalism and media studies"--
Includes bibliographical references and index.
Keywords: News agencies; Foreign news